Cocaine use and HIV-infection modify coronary plaque morphology differently than conventional cardiovascular risk factors. (25th November 2020) - Kolossvary, M; Bluemke, D.A; Fishman, E.K; Gerstenblith, G; Mandler, R.N; Kickler, T.S; Chen, S; Bhatia, S; Lai, S; Lai, H
Abstract: Background/Introduction: Cardiovascular risk factors are assumed to propagate coronary artery disease (CAD) through the lipid and/or inflammatory pathologic pathways. However, we currently do not have any in-vivo information whether these effects may alter CAD morphology and structure differently. Purpose: We wished to assess whether conventional cardiovascular risk factors (which are assumed to affect CAD primarily through the lipid pathway), and unconventional risk factors such as cocaine use and human immunodeficiency virus (HIV)-infection (which are assumed to propagate CAD primarily through the inflammatory pathway) affect different coronary plaque structures as assessed by radiomics. Methods: In our prospective longitudinal observational study of 300 individuals without cardiovascular symptoms but with coronary CT angiography (CCTA)-confirmed atherosclerosis (210 male, age: 48±7 years) of whom 161 were cocaine users at baseline with or without HIV-infection (226 HIV-infected), underwent CCTA at two time points (mean follow-up: 4.0±2.3 years). Precision phenotyping of CAD was done by calculating 1276 radiomic features on the 861 plaques. Linear mixed models corrected for plaque volume, high-sensitivity C-reactive protein, statin use and positive family history were used to assess the effects of chronic cocaine use, HIV-infection and elevated atherosclerotic cardiovascular disease risk (ASCVD≥7.5%). Hierarchical clustering was used to assess potential clusters among significant radiomic features. Bonferroni corrected p<0.00004 (0.05/1276) was considered significant. Results: Overall, 32.0% (409/1276) of the radiomic features showed any significant association, of which 74.1% (303/409), 4.2% (17/409) and 25.4% (104/409) were affected by cocaine use, HIV-infection and elevated ASCVD risk, respectively. There was no overlap among radiomic features significantly associated with increased ASCVD risk and cocaine use or HIV-infection, while 88, 2% (15/17) of HIV-infection associated parameters were also affected by cocaine use. Cluster analysis indicated 13 different structural components among significant features, of which eight were unique to chronic cocaine use, three unique to ASCVD risk, and two contained parameters associated with chronic cocaine use, elevated ASCVD risk and/or HIV-infection. Interpretation: Chronic cocaine use and HIV-infection modify different CAD morphological components than conventional cardiovascular risk factors, potentially implying independent pathological pathways of disease progression irrespective of each other. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health, National Institute on Drug Abuse